AN ANALYSIS ON SUSTAINABILITY OF SHARK UTILIZATION USING FISH RESOURCES AND FISHING TECHNIQUES APPROACH IN SELAYAR ISLAND REGENCY - Nawawi, Ziaul Haq; Nessa, Natsir; Yanuarita, Dewi; Yusuf, Muhammad Yusfi; Sainal, Sainal (Jurnal Ilmu Kelautan SPERMONDE, 2020)
The research aims to record the types of shark utilization in Selayar Islands Regency, explore the spread and shark status of the Regency of Selayar Islands, and examine the sustainability status of shark utilization by fisherman in Selayar Islands. The research method was based on the assessment of EAFM indicator assessments to assess the performance of shark resource management on Tarupa Island, Rajuni Island, Polassi Island and Kayuadi Island Selayar Islands Regency with an indicator approach involving two domains, i.e (1) Fish resources and (2) Fishing technique. The methods of obtaining the data were survey by extracting the data through interviews/questionnaire. The sample was determined using purposive sampling technique. The results of the research indicate that the status of utilizing shark fishery in Selayar Islands Regency is currently in medium category. The main issues indicated are a decrease in catch size and the catch of sharks that are not feasible to catch (50% of catch <Lm). The domains that need to get primary attention in the management of sharks fisheries are the domains of fish resources and fishing technique. The efforts of management carried out in each fields are based on central issues that emerge. Connectivity efforts between communities and institutions are needed to produce functional fisheries management status so that the sustainability of shark resources in Selayar Islands Regency can be sustainable